A versatile nanoplatform for synergistic combination therapy to treat human esophageal cancer - WANG Xin-shuai; KONG De-jiu; LIN Tzu-yin; LI Xiao-cen; IZUMIYA Yoshihiro; DING Xue-zhen; ZHANG Li; HU Xiao-chen; YANG Jun-qiang; GAO She-gan; LAM Kit S; LI Yuan-pei (Acta Pharmacologica Sinica, 2017)
One of the major goals of precision oncology is to promote combination therapy to improve efficacy and reduce side effects of anti-cancer drugs based on their molecular mechanisms. In this study, we aimed to develop and validate new nanoformulations of docetaxel (DTX) and bortezomib (BTZ) for targeted combination therapy to treat human esophageal cancer. By leveraging our versatile disulfide cross-linked micelles (DCMs) platform, we developed nanoformulations of DTX and BTZ (named DTX-DCMs and BTZ-DCMs). Their physical properties were characterized; their anti-cancer efficacies and mechanisms of action were investigated in a human esophageal cancer cell line in vitro. Furthermore, the in vitro anti-tumor activities of combination therapies (concurrent drug treatment, sequential drug treatment, and treatment using different ratios of the drugs) were examined in comparison with the single drug treatment and free drug strategies. These drug-loaded nanoparticles were spherical in shape and relatively small in size of approximately 20–22 nm. The entrapment efficiencies of DTX and BTZ into nanoparticles were 82.4% and 84.1%, respectively. The drug release rates of DTX-DCMs and BTZ-DCMs were sustained, and greatly increased in the presence of GSH. These nanodrugs were effectively internalized by KYSE30 esophageal cancer cells, and dose-dependently induced cell apoptosis. We further revealed a strong synergistic effect between DTX-DCMs and BTZ-DCMs against KYSE30 esophageal cancer cells. Sequential combination therapy with DTX-DCMs followed by BTZ-DCMs exhibited the best anti-tumor efficacy in vitro. This study demonstrates that DTX and BTZ could be successfully nanoformulated into disulfide cross-linked micelles. The nanoformulations of DTX and BTZ demonstrate an immense potential for synergistic combination therapy to treat human esophageal cancer.